2022
DOI: 10.3389/fphar.2022.821940
|View full text |Cite
|
Sign up to set email alerts
|

Progress on the Elucidation of the Antinociceptive Effect of Ginseng and Ginsenosides in Chronic Pain

Abstract: Ginseng (Panax ginseng C.A. Meyer) is a traditional Oriental herbal drug widely used in East Asia. Its main active ingredients are ginsenosides whose constituents are known to have various pharmacological activities such as anticancer, antinociception, and neuroprotection. The analgesic effects of ginsenosides, such as Rg1, Rg2, and Rb1, as well as compound K, are well known and the analgesic mechanism of action in inflammatory pain models is thought to be the down regulation of pro-inflammatory cytokine expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…is a perennial herbaceous plant in the family Araliaceae that is primarily distributed in China, South Korea, and Russia (Abid et al, 2021 ). Ginseng is traditional and precious medicine in East Asia and has important medicinal and economic value (Li et al, 2022 ). The main active compounds in ginseng include ginsenosides, polysaccharides, and polypeptides, among others (Ratan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…is a perennial herbaceous plant in the family Araliaceae that is primarily distributed in China, South Korea, and Russia (Abid et al, 2021 ). Ginseng is traditional and precious medicine in East Asia and has important medicinal and economic value (Li et al, 2022 ). The main active compounds in ginseng include ginsenosides, polysaccharides, and polypeptides, among others (Ratan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ]. To date, numerous studies have revealed various beneficial effects of P. ginseng and its derivatives, including ginsenosides, for the manipulation of fatigue [ 15 ], diabetes [ 16 ], chronic pain [ 17 ], and systemic inflammation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 200 types of ginsenosides have been identified in ginseng, including Rb1, Rb2, Rg1, Rd, Rh1, and Rh2. Increasing clinical and experimental evidence indicates that ginsenosides have different advantageous effects on various diseases [9][10][11][12]. Ginsenoside Rh2 is a major bioactive component of red ginseng extract.…”
Section: Introductionmentioning
confidence: 99%